Who earns minimum wages in Europe? New evidence based on household surveys - Rycx, François; Kampelmann, Stephan (Brussels, 2013)
"This paper aims to provide a comprehensive, evidence-based, and up-to-date assessment of minimum wages in a range of European countries. A first step towards a better understanding of where Europe stands today on this issue requires to grasp the diversity of European minimum wage systems, a key objective of the paper at hand. The second objective is to document international differences in the so-called "bite" of the minimum wage. This leads to questions such as "how do national minimum wages compare to the overall wage distribution?" and "how many people earn minimum wages in each country?" that are assessed for a set of nine countries from Western, Central and Eastern Europe: Belgium, Bulgaria, Germany, Hungary, Ireland, Poland, Romania, Spain, and the United Kingdom. This sample was designed to include countries for which recent evidence has been missing prior to this paper. What is more, the study also overcomes the narrow focus of extant overviews that have typically focussed only on full-time employment. Crucially, the study improves on existing work by looking beyond aggregate numbers; it provides a detailed panorama of the population of minimum wage earners in each country under investigation, notably by describing their composition in terms of a range of socio-demographic characteristics."